History education research in Türkiye: A bibliometric analysis based on WOS and Scopus data (2000-2023) - Erkan Bozkurt (Turkish History Education Journal)
This study aims to exhibit a bibliometric analysis of history education research in Türkiye. A total of 127 documents from 70 sources indexed in the Web of Science and Scopus databases in the years 2000-2023 were used in the analysis. The analysis provides a review of history education research in Türkiye by identifying the dynamics of research by presenting a wide in-depth knowledge concerning the periodical process, current situation, and future directions. Since 2006, history education studies in Türkiye have become more visible in the relevant databases. The annual increase rate of the studies was determined as 8.49 percent. Among the 127 documents accessed, research articles are the most common with a total of 104 articles. From the analysis, it could be said that history education research in Türkiye is mostly conducted in Turkish journals and by Turkish authors. Compared to international literature in history education, studies on ‘historical consciousness’ in Türkiye that were indexed in WOS and Scopus databases were found to be rare in the analysis. Despite this, it is observed that new approaches have started to be studied within the framework of concepts such as 'oral history', 'postmodernism', and 'museum education' in history education studies originating from Türkiye that were indexed in WOS and Scopus databases. In the analysis, it has been observed that although academic studies in qualified databases originating from Türkiye in the field of history education are not sufficient, they have been on an increasing trend in recent years.